2021
DOI: 10.23887/jet.v5i2.33813
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of HOTS-Based Science Questions Developed by Indonesian Elementary School Teachers

Abstract: In Indonesia, several training pieces have been conducted to develop HOTS-based science questions for elementary school teachers. However, few studies examine how elementary school teachers developed HOTS-based science questions. Hence, the current study is a case study that aims to analyze HOTS-based science questions developed by elementary school teachers in Indonesia. This study employed a descriptive-analytical method by analyzing 60 HOTS-based science questions developed by elementary school teachers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…With reference to the review on the lesson plans, the pre-service teachers had yet to be capable of integrating mistakes with misconceptions. The result of this current research pinpointed that the pre-service teachers with low level of CK indicated that they had no adequate competence to convert contents, which resulted in incompetence primarily in selecting the best teaching method needed to accommodate the teaching of Science for elementary school students (Leader-Janssen & Rankin-Erickson, 2018), especially the one fostering HOTS (Ishartono et al, 2021). The correlational calculation between CK and PK through simple linier regression (Figure 1) indicates p-value = 0.000, which means that both correlated significantly.…”
Section: Resultsmentioning
confidence: 92%
“…With reference to the review on the lesson plans, the pre-service teachers had yet to be capable of integrating mistakes with misconceptions. The result of this current research pinpointed that the pre-service teachers with low level of CK indicated that they had no adequate competence to convert contents, which resulted in incompetence primarily in selecting the best teaching method needed to accommodate the teaching of Science for elementary school students (Leader-Janssen & Rankin-Erickson, 2018), especially the one fostering HOTS (Ishartono et al, 2021). The correlational calculation between CK and PK through simple linier regression (Figure 1) indicates p-value = 0.000, which means that both correlated significantly.…”
Section: Resultsmentioning
confidence: 92%
“…The process and evaluation of learning have not been maximized and the results have not met the minimum passing mark. According to Khair et al (2022) the teaching materials used still involve more textbooks and the worksheets used are still contained in the books so students are not accustomed to solving problems that require higher-order thinking skills (Ishartono et al 2021;Kosasih et al 2022). The learning method used is still dominated by conventional methods or lectures, which are more teacher-centered (Gunawan 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To assess these abilities, problems with context are required (Widana et al, 2019), allowing students to analyze, evaluate, and create. This is supported by Ishartono et al (2021) statement regarding the characteristics of HOTS problems, one of which requires information in its resolution. Various mathematical problems used to measure students' mathematical literacy have intersections in their components, namely problems that are contextual in nature.…”
Section: Rq4 Mathematical Problems Used To Measure Mathematical Literacymentioning
confidence: 88%